High Light Induced Alka(e)ne Biodegradation for Lipid and Redox Homeostasis in Cyanobacteria - Qiao, Yue; Wang, Weihua; Lu, Xuefeng (Frontiers in Microbiology, 2020)
Cyanobacteria are the oldest photosynthetic microorganisms with good environmental adaptability. They are ubiquitous in light-exposed habitats on Earth. In recent years，cyanobacteria have become an ideal platform for producing biofuels and biochemicals from solar energy and carbon dioxide. Alka(e)nes are the main constituents of gasoline, diesel and jet fuels. Alka(e)ne biosynthesis pathways are present in all sequenced cyanobacteria. Most cyanobacteria biosynthesize long chain alka(e)nes via acyl-acyl-carrier proteins reductase (AAR) and aldehyde-deformylating oxygenase (ADO). Alka(e)nes can be biodegraded by a variety of cyanobacteria, which lack a β-oxidation pathway. However, the mechanisms of alka(e)ne biodegradation in cyanobacteria remain elusive. In this study, a cyanobacterial alka(e)ne biodegradation pathway was uncovered by in vitro enzyme assays. Under high light, alka(e)nes in the membrane can be converted into alcohols and aldehydes by ADO, and aldehyde dehydrogenase (ALDH) can then convert the aldehydes into fatty acids to maintain lipid homeostasis in cyanobacteria. As highly reduced molecules, alka(e)nes could serve as electron donors to further reduce partially reduced reactive oxygen species (ROS) in cyanobacteria under high light. Alka(e)ne biodegradation may serve as an emergency mechanism for responding to the oxidative stress generated by excess light exposure. This study will shed new light on the roles of alka(e)ne metabolism in cyanobacteria. It is important to reduce the content of ROS by optimization of cultivation and genetic engineering for efficient alka(e)ne biosynthesis in cyanobacteria.